Testicular Histomorphometric Evaluation of Zebu Bull Breeds - Paulo Antônio Terrabuio Andreussi; Deiler Sampaio Costa; Fábio José Carvalho Faria; Carlos Antônio Carvalho Fernandes; Marcelo Diniz Santos; Juliana Correa Borges Silva (Brazilian Archives of Biology and Technology, 2014)
The objective of this study was to evaluate the quantitative histology and testicular biometrics in zebu bulls of different breeds. Testicular fragments of Nelore (n=10), Polled Nelore (n=6), Gir (n=5), Guzerat (n=5) and Tabapuã bulls (n=5) were used. The fragments were perfusion-fixed in Karnovsky solution, embedded in glycol methacrylate and stained with toluidine blue-1% sodium borate. The Nelore animals had a higher tubular volumetric proportion (85.2%) and greater height of the seminiferous epithelium (73.2 µm) than the Gir, Guzerat and Tabapuã breeds. The Nelore animals also had a higher volumetric proportion of Leydig cells (5.2%) than the Guzerat and Tabapuã breeds. There was no significant difference for any of these parameters between the Nelore and Polled Nelore breeds. The gonadosomatic index, seminiferous tubule diameter, cross-sectional area of the seminiferous tubule and tubule length (total length and length per gram of testicular parenchyma) did not vary among the breeds studied. The morphometric parameters evaluated suggested that the genetic selection applied to the Nelore and Polled Nelore breeds improved the efficiency of spermatogenesis in these breeders.